GAZA WAR: FROM IDENTITY POLITICS TO POLARIZATION IN THE WESTERN FOREIGN POLICY - BONTEA, George Horațiu (Studia Universitatis Babes-Bolyai Studia Europaea, 2023)
One of the trickiest conflicts in the Middle East and North Africa has reopened as a result of the October 7 terrorist strikes. Open discussions were however halted by Hamas' unilateral strike, even though the two-state solution appeared increasingly likely with the Palestinian Authority serving as the future structural restructuring of #FreePalestine. The situation in the Gaza Strip caused a great deal of divisiveness in western public opinion in addition to internal conflicts and tensions. So, the purpose of this paper was to provide a poststructuralist analysis of the dominant academic viewpoints on the state of affairs between Israel and Palestine. The relationship between identity and foreign policy is examined in this study by utilising the primary methodological instruments of reflectivist international relations theory, including intertextuality, genealogy, discourse analysis, and deconstruction. They study both epistemological and ontological aspects because of the theoretical framework, and the narratives of "us and them" were and continue to be important components in the history and current circumstances of the Gaza Strip. The findings provide context for the significance of Hamas' rhetoric and the monopoly of power, as well as outlining the identitarian divide between Palestinians in Gaza and the West Bank.